Decompositions of Complete Multigraphs into Cyclic Designs - Alqadri, Mowafaq; Ibrahim, Haslinda; Karims, Sharmila (Society of Visual Informatics, and Institute of Visual Informatics - UKM and Soft Computing and Data Mining Centre - UTHM, 2020)
Let and be positive integer, denote a complete multigraph. A decomposition of a graph is a set of subgraphs of whose edge sets partition the edge set of . The aim of this paper, is to decompose a complete multigraph into cyclic - cycle system according to specified conditions. As the main consequence, construction of decomposition of into cyclic Hamiltonian wheel system, where , is also given. The difference set method is used to construct the desired designs